2021
DOI: 10.1016/j.scitotenv.2021.147183
|View full text |Cite
|
Sign up to set email alerts
|

The presence of SARS-CoV-2 RNA in different freshwater environments in urban settings determined by RT-qPCR: Implications for water safety

Abstract: This study is the first focused on the presence of SARS-CoV-2 in different freshwater environments in an urban setting. Groundwater and surface water reservoirs for drinking water as well as water from receiving rivers of the Monterrey Metropolitan Area were sampled repeatedly during a SARS-CoV-2 peak phase between October 2020 and January 2021, and viral RNA was measured by quantitative reverse transcription polymerase chain reaction. Forty-four percent of the groundwater samples had detectable viral loads be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 59 publications
3
37
0
Order By: Relevance
“…Possible implications of the SARS-CoV-2 environmental shedding by wastewaters are the contamination of surface waters and its possible spill over to the wildlife. Even though SARS-CoV-2 RNA was detected in open surface waters ( Kolarević et al, 2021 ; Mahlknecht et al, 2021 ; Rimoldi et al, 2020 ), there is no evidence for a transmission of SARS-CoV-2 via water-food-environmental media ( Adelodun et al, 2021 ). To this date SARS-CoV-2 pandemic strain was not detected to circulate in free-ranging wildlife species which may be in contact with surface waters, wastewaters and human waste in general ( Colombo et al, 2021 ; Jemeršić et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Possible implications of the SARS-CoV-2 environmental shedding by wastewaters are the contamination of surface waters and its possible spill over to the wildlife. Even though SARS-CoV-2 RNA was detected in open surface waters ( Kolarević et al, 2021 ; Mahlknecht et al, 2021 ; Rimoldi et al, 2020 ), there is no evidence for a transmission of SARS-CoV-2 via water-food-environmental media ( Adelodun et al, 2021 ). To this date SARS-CoV-2 pandemic strain was not detected to circulate in free-ranging wildlife species which may be in contact with surface waters, wastewaters and human waste in general ( Colombo et al, 2021 ; Jemeršić et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 has been detected by real-time reverse transcription-PCR (RT-PCR) in fecal samples ( 1 ) and in municipal wastewater ( 2 ), and transmission associated with sewage aerosols was documented during the 2003 outbreak of the closely related SARS-CoV coronavirus ( 3 ). Recently, SARS-CoV-2 was detected in groundwater, rivers, and dam water in the Monterrey, Mexico, region ( 4 ). These observations raise critical questions about the adequacy of treatment for drinking water and wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Núñez-Delgado (2020) and Kumar et al (2020) raised a concern about SARS-CoV-2 presence in the environmental compartments and the potential risks of transmission through water-soil media while extending to the groundwater sources. A recent study by Mahlknecht et al (2021) reported the presence of SARS-CoV-2 RNA in different freshwater environments in an urban setting including groundwater samples, which demonstrates the ability of the virus to leach and infiltrate from surface water or leakage sewer to underground water resources. A review study by Bradford et al (2013) had earlier described the fate and transport of viruses in the environmental compartment, while a study by Ogorzaly et al (2010) demonstrated the transport of enteric viruses through the aquifer into groundwater.…”
Section: Water-food-environmental Compartments Associated Sars-cov-2 Transmissionmentioning
confidence: 94%